Effects of second order dispersion in free space optical communication - Yap D.F.W.; Wong V.C.; Koh S.P.; Tiong S.K.; Mohd Tahir M.A.E. (2023)
Free Space Optic (FSO) can be considered as an attractive option to fiber optic. FSO has the capability to go beyond the limit of fiber optics. Unfortunately, due to the effects of dispersion in the atmosphere, FSO, as a point-to-point communication system that requires line-of-sight transmission; suffers from attenuation and signal loss. Thus, practical and detailed research is needed to improve this wireless system. In this study, simulation on FSO propagation using measured parameter values was carried out in order to gain better understanding on the pulse behavior in free space with better level of accuracy. Using MATLAB and experimental parameter values, a more precise model can be obtained and analyzed. This will allow some level of prediction on the behavior of the propagating light pulse in the atmosphere and subsequently the FSO system performance can be further improved. 2010 Asian Network for Scientific Information.